Model Penyelesaian Pemutusan Hubungan Kerja Antara Indonesia dan Malaysia - Yanti, Helen; Rahmani, Hendra; Indarto, Indarto; Murdiani, Liza Aisyah; Charda S , Ujang (Universitas Medan Area, 2026)
Termination of Employment (PHK) is a crucial issue in industrial relations, often arising from labor disputes, particularly concerning the misuse of Fixed-Term Employment Agreements (PKWT). The differences in regulation and mechanisms for resolving terminations between Indonesia and Malaysia reflect distinct characteristics of labor law systems in providing legal protection for both employees and employers. This study aims to analyze the models of termination resolution in Indonesia and Malaysia, focusing on three main aspects: severance pay regulation, termination procedures, and labor dispute resolution institutions. The research method employed is normative legal research with statutory, comparative law, and case study approaches. The case study used is PT HS, which illustrates the practice of resolving labor disputes prior to termination through labor supervision mechanisms by the Manpower Office. The study findings indicate that the termination resolution model in Indonesia is procedural and tiered, with active government involvement, but tends to require a lengthy timeframe. This study is expected to contribute to the development of a more effective and equitable model for termination resolution.